Cyclic behaviour of as-built and strengthened existing reinforced concrete columns previously damaged by fire. (1st September 2022) - Melo, José; Triantafyllidis, Zafiris; Rush, David; Bisby, Luke; Rossetto, Tiziana; Arêde, António; Varum, Humberto; Ioannou, Ioanna
Highlights: First experimental ciclic tests performed on RC retrofited columns which have previously suffered damage from realistic fire exposures. Experimental campaign carried out on six full-scale RC columns with detailing representing existing Mediterranean buildings designed to old seismic codes are subjected to fire and then cyclic loading. Assessement of a strengthening method used to increase the concrete strength through confinement and to increase the displacement ductility and energy dissipation capacity under seismic loading. Temperature evolution obtained during the fire exposures in two cross-sections of the columns. Comparisons of force–displacement global responses, dissipated energy evolutions, strength degradation and observed damage of the tested columns. Abstract: A structure, during its life, may be subjected to multiple hazards. These hazards are sometimes combined over a short period of time, or in some cases occur many years apart, with the first hazard influencing the structural response under a second hazard. A reinforced concrete (RC) structure previously damaged by fire and then exposed to seismic loading is one such example. To assess such structures, the effects of fire on the cyclic performance of RC elements needs to be better understood. Moreover, it is also important to develop and validate strengthening methods that can reinstate or improve the seismic performance of fire-damaged RC elements. This paper presents the results of a novel experimental campaign where six full-scale RC columns with detailing representing existing Mediterranean buildings designed to old seismic codes are subjected to fire and then cyclic loading. Four RC columns were damaged after exposure to 30 or 90 min of the ISO 834 standard fire curve in a furnace and then tested under uniaxial cyclic lateral loading up to failure. Two of these columns were repaired and strengthened post-fire with Carbon Fibre Reinforced Polymer (CFRP) wrapping. The strengthening method aimed to increase the concrete strength through confinement, and to increase the displacement ductility and energy dissipation capacity under seismic loading. Two additional control columns, one as-built and another strengthened, were cyclically tested for comparison with the fire-damaged columns. It was found that the 30 min fire exposure resulted in few concrete cracks, whilst cover spalling and general cracking was observed in the 90 min fire exposure. A significant decrease in the displacement ductility and dissipated energy of the columns was observed following fire exposure, even for the 30 min fire. The columns that had post-fire repair and CFRP strengthening, showed better cyclic performance than the control column without fire exposure. It was also found that post-fire strengthened columns may reach similar seismic performance than similarly strengthened columns without previous fire damage.